Pengaruh PAD, DAU, DBH dan DAK terhadap Belanja Daerah pada Kabupaten/Kota di Provinsi Jawa Tengah 2018-2023 - Arisrianto, Sugeng; Santosa, Agus Budi (Riwayat: Educational Journal of History and Humanities, 2025)
This study aims to analyze the influence of Local Own-Source Revenue (PAD), General Allocation Fund (DAU), Revenue Sharing Fund (DBH), and Special Allocation Fund (DAK) on Local Expenditure in 35 districts/cities in Central Java Province for the period 20182023. The background of the study is based on the low fiscal autonomy ratio of the province, which averages only 40.98%, indicating a high dependence on central government transfers. The data used are panel time series data obtained from the official website of the Directorate General of Fiscal Balance and other secondary sources. The analysis was conducted quantitatively using descriptive statistics, classical assumption tests (normality, multicollinearity, heteroskedasticity, autocorrelation), and multiple linear regression using SPSS version 30 to test the influence of each independent variable on regional expenditure. The results of the study indicate that all independent variables, namely PAD, DAU, DBH, and DAK, have a positive and significant effect on Regional Expenditure, with a coefficient of determination (R) of 0.979, meaning that 97.8% of the variation in regional expenditure can be explained by these four variables. PAD and DAU make the dominant contributions, while DBH and DAK, although having a smaller impact, remain statistically significant. The research conclusion emphasizes the importance of optimizing PAD as a source of regional revenue and the effectiveness of the distribution and utilization of central government transfer funds. These findings have implications for local governments to enhance fiscal autonomy through innovative PAD management, while strategically utilizing fiscal transfers to strengthen spending capacity and public services.